Transition metal chlorides complexes with tetrahydrofuran [MtCl(4)(THF)(2)] used as precursors of ethylene polymerization - Szczegot, K.; Flisak, Z.; Sibelska, I.; Dawidowska-Marynowicz, B. (Polimery, 2022)
Three complexes of transition metal chlorides with tetrahydrofuran (THF), viz., [TiCl4(THF)(2)] (I), [ZrCl4(THF)(2)] (II), and [HfCl4(THF)(2)] (III), were prepared and studied as the precursors of titanium-magnesium catalysts to be used in low-pressure polymerization (0.5 MPa, 323 K) of ethylene using AlEt3 (most favorable), AlEt2Cl, or Al(i-Bu)(3) as cocatalysts. The activity of catalysts increases in the order [HfCl4(THF)(2)] < [ZrCl4(THF)(2)] < [TiCl4(THF)(2)]. Degree of crystallinity (C), density, bulk density, M, MWD, and m.p. were determined for the resulting HDPE. Catalyst activity, found to obey the following ascending type (III) < (II) < (I), increased as the element electronegativity was raised and the partial charge on the transition metal atom in the precursor was diminished. The catalyst surface patterns visualized by a computer supported the experimental data. The uncomplexed, [MgCl2(THF)(2)]-supported tetrachlorides yielded catalysts less active than (I)-(III), but following the same general activity correlations.